Unusual Enhancement of the Optical Depth on the Continental Shelf Depth Latitudinal Variation in the Stratospheric Polar Vortex - Ziqiang Xu; Yuanyuan Qian; Taiping Yang; Fuying Tang; Yuhan Luo; Fuqi Si (Remote Sensing, 2023)
The Antarctic ozone hole has attracted attention concerning global climate change. Breakthroughs regarding ozone observation methods and the formation principles of ozone holes have occurred. This study compared the slant column ozone obtained from SCanning Imaging Absorption SpectroMeter for Atmospheric CHartographY (SCIAMACHY) Level 1 optical spectroscopy data processed by QDOAS software with that reconstructed from SCIAMACHY Level 2 ozone data using geographic information to obtain the optical depth coefficients. The global distribution of optical depth coefficients reveals latitudinal homogeneity, whereas the distribution of coefficients in the polar regions reveals heterogeneity. This heterogeneity has an annual variation pattern, alternating between strong and weak distributions in the Arctic and Antarctic regions. It is most evident in the Palmer Peninsula of Antarctica, where the optical depth coefficients were significantly higher than those of the surrounding regions at the same latitude. This analysis excluded the atmospheric pressure influence and suggested the influence of the continental shelf depth. The protrusion of the continental shelf depth changes the optical depth coefficients owing to the geographical proximity of the Antarctic Palmer Peninsula to South America, which separates the Atlantic and Pacific Oceans in an east–west direction.